Development of the Standard Spelling Ability of Upper Elementary Students with Reading Disabilities through the 5-Step Ladder Teaching Technique Integrated with Recreational Songs - Saengthong, Amorat; Chaiklam, Sukunyasopee (ARU Research Journal Humanities and Social Sciences, 2026)
The purposes of this research were 1) to determine the effectiveness of learning management for phonetic reading using the 5-Step Ladder technique combined with recreational songs for students with learning disabilities in reading; 2) to compare the phonetic reading abilities of upper elementary students before and after the intervention; and 3) to study the students’ happiness levels towards this teaching approach. The sample consisted of 4 upper elementary school students with learning disabilities in reading. The research instruments included 10 lesson plans, a pre-test and post-test of reading ability, and a learning happiness assessment scale. Data were analyzed using the Effectiveness Index (E.I.), Mean, Median, and Standard Deviation (S.D.). The results showed that the learning management achieved an Effectiveness Index of 0.7059 (70.59%). The students’ post-test phonetic reading ability (Median = 13.00) was higher than their pre-test ability (Median = 2.50). Furthermore, the students’ happiness towards the learning management was at a "Good" level (X ̅= 3.00, S.D.= 0)